The erasure of infection-associated chronic conditions: Critical interpretive synthesis of literature on healthcare for long COVID and related conditions in Brazil - Flora Cornish; Brenda Sabaine; Letícia Soares; Barbara Caldas; Margareth Crisóstomo Portela; Aylene Bousquat; Emma-Louise Aveling (Global Public Health)
Evidence is emerging that long COVID is at least as prevalent in the Global South as the Global North, but literature on long COVID healthcare in the Global South is in its infancy. Brazil is seeing significant levels of debility due to long COVID but a limited national evidence-base. long COVID shares symptomatology and appropriate care with a wider category of infection-associated chronic conditions (IACCs). This article reviews literature published between 2000 and 2023 addressing healthcare for long COVID and IACCs in Brazil, in the interest of exploring challenges and opportunities for the SUS (Brazil’s universal health system) to offer appropriate long COVID healthcare. We find that long COVID and IACCs collectively are subject to erasure from Brazilian healthcare knowledge, through lack of expertise, a resource-limited health system prioritising urgent care, and the concentration of poor health in marginalised populations with limited decision-making power. A nascent intellectual will to address long COVID, and a tradition of social participation in healthcare governance present potential opportunities. We call for ignition of a global step-change in tackling healthcare for long COVID and IACCs. Global equity in long COVID healthcare requires the development and sharing of expertise regarding its universal and context-specific features.